Tugas Guru di Kelas dalam Implementasi Kurikulum Merdeka: Perspektif Islam - Siti Aminah; Mukh Nursikin (Journal on Education, 2023)
This research is a type of qualitative research with a descriptive method. Data is collected through documentation, observation and interviews. The data analysis technique researchers use is the flow model, which includes data reduction and conclusion. The subjects in this study are principals, teachers, and students, while the object of this study is the classroom teachers’ task to implement an independent curriculum. This study analyzes how the Islamic view relates to teachers’ tasks in implementing the Independent Curriculum. The results showed that SMP Negeri 3 Salatiga has implemented the Merdeka Curriculum in grade 7. In implementing the independent curriculum, teachers serve as facilitators and carry out learning based on the principles of independent learning. The duties of teachers and the principles of learning in the Merdeka Curriculum are in accordance with Islamic teachings and have been explained in the Qur'an and hadith.